Brics’ Foreign Debt Burden and its Impact on Core Institutional Basis - Akhmadeev, Ravil Gabdullaevich; Bykanova, Olga Alekseevna; Turishcheva, Tatiana Borisovna (Journal of Reviews on Global Economics, 2018)
Creation of a multipolar international economy and economic relations is accompanied by shifting gravity centers of international finances, redistribution of positions on the global market for financial services in favor of large emerging countries and countries with transitional economies. This post crisis period triggered serious problems related to international capital inflows and outflows at the BRICS states. This is all due to a slow recovery of developed countries; a high probability of a full-scale debt crisis in some E.U. states; mounting uncertainties following financial reforms in some states, etc. But raising debt as an important way to finance speedy economic growth and import of technologies to the BRICS countries make their financial systems more vulnerable to exogenous stresses and shocks, which result in an unreasonable firming of national currencies. In our research, we have identified the risks and misbalances of global development, which affect BRICS, evaluated the influence of foreign debt and singled out the key growth trends. We have revealed the importance of the New Development Bank development, which will help solve urgent problems of its participants connected with their growing role in international economic relations: the creation of a regional financing mechanism as well as a core institutional basis to represent BRICS’ interests in the global financial structure and to become the missing link in interaction with global financial institutions.